Having to manage: culturally and linguistically diverse mothers' lived experiences with sustained nurse home visiting programs - Mehrnoush Bonakdar Tehrani; Kelly Baird; Suza Trajkovski; Lynn Kemp (BMC, 2023)
Abstract Background Culturally and linguistically diverse (CALD) mothers with young children with limited English proficiency (LEP) encounter multiple barriers in accessing and engaging with primary healthcare services. The aim of this study was to explore the lived experiences and perceptions of CALD mothers with LEP in receiving child and family health nursing (CFHN) services and sustained nurse home visiting (SNHV) programs. Methods Fourteen mothers were interviewed from two large Local Health Districts in Sydney. All interviews were audio-recorded for transcription purposes. Interpretative Phenomenology Analysis (IPA) was used for analysis and the socioecological approach was applied to interpret the data. Results CALD mothers with LEP experienced both challenges and facilitators in their access and engagement with CFHN services and SNHV programs that were identified in four themes: managing culture; managing the service system; managing the relationship; and strengths and weaknesses of CFHN services. Conclusion The integration of strategies such as building trusting relationships, using female professional interpreters and better understanding of CALD mothers' cultural practices may address CALD mothers' needs and facilitate communication. Design and development of model of support involving CALD mothers with LEP in ways that voice their ideas could meet their needs and contribute to better engagement of this vulnerable population with CFHN services and SNHV programs.